Strategies to Increase Profitability by Using Digital-Based Sales in Micro, Small and Medium Enterprise (MSMEs) in Medan City - Siahaan, Audrey M.; Siboro, Danri T.; Nainggolan, Melvin Sanro Jacobest (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Using Internet networks facilitates the distribution, sale, purchase, and promotion of products (goods and services) through digital platforms such as social media and e-commerce. One practical approach to enhancing profitability involves leveraging social media platforms as marketing and sales channels alongside utilizing e-commerce. The selected subject of analysis pertains to the proprietors of MSMEs engaged in Internet commerce inside the city of Medan. The study will involve a sample size of 40 MSMEs selected by the purposive sampling technique. The method employed for data collecting involves the utilization of a questionnaire. Data analysis techniques employed include data quality testing, classical assumption testing, and hypothesis testing using linear and moderation regression analysis. The findings indicate that implementing a Social Media Strategy has a favorable and statistically significant impact on MSMEs profitability in Medan City. Using E-commerce platforms to facilitate digital sales can enhance the relationship between the influence of a Social Media Strategy and the profitability of MSMEs in Medan City. There is an expectation that online business entities will employ methods involving social media and e-commerce while also remaining responsive to technical advancements to enhance and modernize their online business systems, thereby avoiding obsolescence in the face of emerging technologies.